A pilot study to assess use of fluorescent lotion in patient care simulations to illustrate pathogen dissemination and train personnel in correct use of personal protective equipment. Issue 1 (December 2016) - Alhmidi, Heba; Koganti, Sreelatha; Tomas, Myreen; Cadnum, Jennifer; Jencson, Annette; Donskey, Curtis
Abstract Background Simulations using fluorescent tracers can be useful in understanding the spread of pathogens and in devising effective infection control strategies. Methods During simulated patient care interactions in which providers wore gloves and gowns, we evaluated environmental and personnel dissemination of fluorescent lotion and bacteriophage MS2 from a contaminated mannequin. The frequency of skin and clothing contamination after removal of personal protective equipment (PPE) was compared before versus after an intervention that included education and practice in PPE donning and doffing. Results Ten healthcare personnel participated in 30 pre-intervention and 30 post-intervention patient care simulations. Fluorescent lotion and bacteriophage MS2 were rapidly disseminated to touched surfaces throughout the room; there was no difference in the frequency of contamination before versus after the PPE training intervention. After the intervention, there was a decrease in skin and/or clothing contamination with fluorescent lotion (9/30, 30 % versus 1/30, 3 %;P  = 0.01) and bacteriophage MS2 (8/30, 27 % versus 2/30, 7 %;P  = 0.08) and there was a significant reduction in the concentration of bacteriophage MS2 recovered from hands (0.31 versus 0.07 log10 plaque-forming units;P  < 0.01). Conclusions Our findings suggest that simulations with fluorescent lotion can be a useful teaching tool to illustrate the spread of pathogens and provide further evidence that simple PPE training interventions can be effective in reducing contamination of personnel.